Pengembangan Gapura Berbasis Kearifan Lokal Sebagai Upaya Penguatan Identitas Wilayah RT 30 RW 05 Kelurahan Betungan - Martika, Rengga; Rahayu, Melyan Arista; Zhafran, Alif; Efrian, Ahmad jalou; Permana, Jaka; Hanila, Siti; Fitriano, Yun; Susanti, Neri (Utami Publisher, 2025)
A gate (gapura) serves not only as a territorial marker but also as an architectural expression of a community’s cultural identity and local values. However, modernization and lack of attention have led many gates to lose their symbolic significance. This community service program aimed to revitalize the entrance gate at RT 30 RW 05, Betungan Subdistrict, Bengkulu City, using a local wisdom-based and community-participatory approach. The research employed a descriptive qualitative method supported by simple quantitative data gathered through questionnaires, observations, interviews, and documentation. The results showed a significant increase in community participation, successful integration of local wisdom elements into the gate design, and improvement in the neighborhood’s image and residents’ pride. The previously generic gate was transformed into a community icon that reflects identity and communal spirit. This program demonstrates that involving local residents in culturally rooted infrastructure development strengthens ownership and promotes positive behavioral changes. The model is recommended for replication in other urban areas to reinforce identity and social harmony.